Developing an Online Leave Application (OLA) / Mohd Ikhsan Md Raus - Md Raus, Mohd Ikhsan (2006)
This project prepared for Administration Department under Faculty of Information Technology and Quantitative Science (FITQS). The prototype of Online Leave Application (OLA) enables staff from this faculty to interact with the system. The target users are academic staffs, which are lecturers, non-academic staffs and administrator. This system contains common online information of staffs, ease to apply the leave, ease submitting the approval applied leave, ease to retrieve up to date of leave information. The main concern is on how staff from anywhere can apply the leave at anytime they want within the UiTM. The objective of this system is to automate the processes of applying and approving the leave. Besides that, it also supported by other functions such as view calendar leave information. Researcher has adopted the research methodology model from book entitled Object-Oriented System Analysis and Design using UML (Simon Bennett, Steve McRobb and Ray Farmer, 2002). Researcher has discussed a lot about the result and findings of knowledge acquisition in the early part of this chapter. This project was conducted using open source technology, which using the OpenACS web application framework including the AOLserver web server, TCL scripting language, and the PostgreSQL relational database management system (RDBMS).